2018
DOI: 10.3390/su10061690
|View full text |Cite
|
Sign up to set email alerts
|

An Information Framework for Facilitating Cost Saving of Environmental Impacts in the Coal Mining Industry in South Africa

Abstract: Coal-mining contributes much to the economic welfare of a country. Yet it brings along a number of challenges, notably environmental impacts which include water pollution in a water scarce country such as South Africa. This research is conducted in two phases. The first phase intends to establish environmental and other challenges brought about by the coal-mining industry through a comprehensive analysis of available literature. Combatting these challenges is costly; consequently, our work investigates how est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also, the enterprises need to select appropriate suppliers, which can also influence the suppliers' environmental behaviours (Mbedzi, Van der Poll, and Van der Poll 2018). The formulation of evaluation criteria must consider various comprehensive factors, such as the customer's environmental protection requirements, government regulations and policies, and its environmental goals.…”
Section: The Intrinsic Link Of Circular Economy Value Chain and Envirmentioning
confidence: 99%
“…Also, the enterprises need to select appropriate suppliers, which can also influence the suppliers' environmental behaviours (Mbedzi, Van der Poll, and Van der Poll 2018). The formulation of evaluation criteria must consider various comprehensive factors, such as the customer's environmental protection requirements, government regulations and policies, and its environmental goals.…”
Section: The Intrinsic Link Of Circular Economy Value Chain and Envirmentioning
confidence: 99%
“…We observed that sustainability could be improved using integrated management accounting systems that would integrate economic and social resources, supporting the view that the aforementioned methods should be combined to measure environmental costs more accurately. Whilst the adoption of EMA was noted to be voluntary and motivated by social structural inspirations and institutional theory in other countries, its adoption in Zimbabwe was observed to be a result of the need to comply to regulations and pressures from law enforcement agents [151].…”
Section: Discussionmentioning
confidence: 99%
“…Be that as it may, honest and regular communication among stakeholders and regulatory authorities remains a best practice. Following the abridged literature review above, the researchers developed a conceptual framework to address the said challenges [16]. The framework underwent a series of iterative reviews based on sets of qualitative propositions elicited from a deeper and next-level review of the coalmining literature.…”
Section: Methodsmentioning
confidence: 99%